Hyponatriämieinduziertes lebensbedrohliches Hirnödem nach Ecstasykonsum = Hyponatremia-induced life-threatening cerebral edema after ecstasy use - Baumann, Stefan; Becher, Tobias; Frambach, Daniel; Wenz, Holger; Kirschning, Thomas; Borggrefe, Martin; Akın, Ibrahim (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2016)
Ecstasy, a psychoactive amphetamine derivative, is a popular party drug. We report the cases of 2 young adults who developed cerebral edema due to hyponatremia. One patient was released from the hospital without any sequelae, whereas the second patient died due to cerebral edema. Severe cases of symptomatic hyponatremia after ecstasy consumption are described in the literature with partially fatal clinical outcomes. Thus, physicians should be aware of early and consequent control of the sodium and choose an interdisciplinary treatment decision.